Coping Style Modifies General and Affective Autonomic Reactions of Domestic Pigs in Different Behavioral Contexts - Krause, Annika; Puppe, Birger; Langbein, Jan (Frontiers in Behavioral Neuroscience, 2017)
Based on individual adaptive strategies (coping), animals may react differently to environmental challenges in terms of behavior and physiology according to their emotional perception. Emotional valence as well as arousal may be derived by measuring vagal and sympathetic tone of the autonomic nervous system (ANS). We investigated the situation-dependent autonomic response of 16 domestic pigs with either a reactive or a proactive coping style, previously selected according to the backtest which is accepted in piglets to assess escape behavior. At 11 weeks of age, the pigs were equipped with an implantable telemetric device, and heart rate (HR), blood pressure (BP) and their respective variabilities (HRV, BPV) were recorded for 1 hour daily over a time period of 10 days and analyzed in four behavioral contexts (resting, feeding, idling, handling). Additionally, the first minute of feeding and handling was used for a short-term analysis of these parameters in 10-s intervals. Data from day 1-3 (period 1) and day 8-10 (period 2) were grouped into two separate periods. Our results revealed general differences between the coping styles during feeding, resting and handling, with proactive pigs showing higher HR compared to reactive pigs. This elevated HR was based on either lower vagal (resting) or elevated sympathetic activation (feeding, handling). The short-term analysis of the autonomic activation during feeding revealed a physiological anticipation reaction in proactive pigs in period 1, whereas reactive pigs showed this reaction only in period 2. Food intake was characterized by sympathetic arousal with concurrent vagal withdrawal, which was more pronounced in proactive pigs. In contrast, neither coping style resulted in an anticipation reaction to handling. Vagal activation increased in reactive pigs during handling, while proactive pigs showed an increase in sympathetically driven arousal in period 2. Our findings confirm significant context-related differences in the general autonomic reaction of pigs with different coping styles. Additionally, the two coping styles differ in their affective appraisal over the time course of the experiment, underlining the importance of taking individual differences into account when studying affect and emotion in humans and animals.